The implementation of using digital game in teaching vocabularies to students at Atarashii Smart Center - Adinda Noviala; Mansur; Dyah Kurniawati (Universitas PGRI Ronggolawe Tuban, 2023)
In the process of learning English, students have to master vocabularies. However, the students have some problems when learning vocabularies. To cope with the students’ problems, the learning process applied game-based learning. The objective of the study entitled “The Implementation of Using Digital Games in Atarashii Smart Center” were to describe the Implementation of digital game in teaching vocabularies and to find the students’ responses toward the implementation of digital game. The subject of this study was the students in Atarashii smart center who joined English class. This study used a descriptive qualitative research design. To gets the data, the researcher employed observation, questionnaire and interview. The researcher used percentage of respondents to get responses. The implementation of digital game in teaching learning process is easy to implemented, but there are some difficulties from the students. Students’ difficulties in learning vocabulary were (1) Most of student found difficulties to memorize and choose the appropriate meaning, (2) Students start to burdened when they have to memorize the vocabulary in limited time, (3) Also still confused in using vocabulary. But students’ responses still show positive results. The students enjoy and enthusiasm to use digital game in their learning process. After finding the difficulties, using digital game to learn vocabulary showed a positive effect. The result showed that learning vocabulary using digital game is better than traditional learning. From the total respondents 42% of the students strongly agree and 18% of the students agree that digital game helped the students to master vocabulary. In conclusion, Digital game clearly has the potential to lead the way into better learning outcomes for young learners, particularly in vocabulary mastery.